ANALYSIS OF PT ASTRA'S FINANCIAL REPORT INTERNATIONAL TBK - Alya Zahwa; Cut Ulya Sabiba; Alya Dhiya Putri Erwin; Lafina Rima Dana; Jariah Abubakar (PT. Radja Intercontinental Publishing, 2026)
Study This aim For analyze performance PT Astra International Tbk finance through approach analysis ratio finances which include ratio liquidity , solvency , profitability , activity , and market ratios during 2019–2023 period . Research This motivated by the importance of evaluation performance finance company conglomerate big , especially in face pressure global economy due to COVID-19 pandemic and phases recovery post-pandemic . Research methods used is method descriptive quantitative with using secondary data in the form of report finance PT Astra International Tbk 's annual earnings from report official companies and the Indonesian Stock Exchange . Data analysis techniques were carried out with calculate and interpret various ratio Financial indicators , including Current Ratio, Debt to Equity Ratio (DER), Return on Assets (ROA), Total Asset Turnover (TATO), Price Earnings Ratio (PER), Price to Book Value (PBV), and dividend yield. show that PT Astra International Tbk own level secure liquidity and solvency , resilient profitability , and efficiency relative activity good . In addition , the market ratio shows that share ASII is at a fair valuation with Power pull investment term strong length . Findings This indicates that PT Astra International Tbk have healthy financial fundamentals and be able to guard stability performance in the middle uncertainty economy .